The sexual century - Person, Ethel Spector (Yale University Press, 1999)
"Over the course of the past century, sexual liberation has transformed the way in which most of us regard our bodies and live our sexual lives. Now a preeminent psychoanalytic theoretician on sex and gender discusses what has gone into this unquiet revolution - the roles played by sexologist and psychoanalysts, antibiotics and birth control, the liberation movements, and Freud's insight that sex has as much to do with the mind as it does with the genitals."--Jacket